(untitled) (Revista Venezolana de Salud Pública, 2018)
The rate of deterioration of fish and its safety are related to the hygienic management of the fish and its conditioning, consuming poorly cooked or raw fish can lead to food poisoning, hepatitis, cholera and parasitism. The dishes regularlyinvolved include sushi, sashimi and ceviche. The parasitic disease is caused by the larval phases of a nematode of the family Anisakidae. The parasite develops as an adult in marine mammals that acquire the disease thanks to the infective L3 form developed in fish. The human consumes poorly cooked fish and acquires L3 larva, causing gastric, intestinal and extraintestinal disease or a gastro-allergic modality. Fourty - five specimens of Mugilcephalus purchased in popular markets, refrigerators and stalls in the city of Barquisimeto were studied. Through the visual inspection we evaluated the freshness index and through microbiological analysis we detected sanitary indicators, fecal contamination and pathogens. A recount of the larvae extracted during the visual inspection and during in vitro digestion, the results indicate that the freshness of the specimens was 8.36 ± 3.28 points. Staphylococcus aureus appeared in 64.7% of the samples. The 82.2% of the specimens showed parasitism, with an average of 24.48 larvae per specimen. Microscopic examination of the parasites present structures that coincide with the genus Anisakis. These larvae are foodborne, so that in the face of symptoms and history of consumption of these products,its important to consider these parasites as etiological agentsof these diseases.